Relationship of variables affecting separation following transesterification of vegetable oil - Hájek, Martin; Skopal, František (Wiley-Blackwell, 2009)
The transesterification of vegetable oils (rapeseed and sunflower oils were used) by low molecular alcohol is the most used method of biodiesel production. A heterogeneous reaction mixture is formed by transesterification containing ester and glycerol phases. Biodiesel is gained by the sedimentation of this mixture. We have studied how separation conditions (independent variables: amount of added water, intensity and time of stirring, etc.) affect the quantity and the quality of both phases (dependent variables). The reaction mixture presents a multivariable system, therefore the statistic method Plackett - Burman was used in the planning of experiments. The multidimensional linear regression was used for the description of the relationship between independent and dependent variables. The mathematical model describing this relationship was created for both types of oil.
Keywords: Biodiesel; sedimentation; separation; multivariable system